P18 Caring for people with intellectual and developmental disabilities (IDD) during the COVID-19 pandemic: a transcontinental study. (26th August 2022) - Horan, Paul; Desroches, Melissa; Marsden, Daniel; Fisher, Kathleen; Stych, Judith; Ailey, Sarah; McMillan, Shirley; Tripp, Henrietta; Wilson, Nathan
Abstract : Background: The COVID-19 pandemic has caused substantial challenges to the support systems of people with intellectual and developmental disabilities (IDD) internationally – this study explored the care experiences of people with (IDD) as reported by nurses in Ireland, the UK, the USA, Canada, Australia and New Zealand. Aim: The aim of this study was to carry out an international investigation into the basic care needs experience of people with IDD one year into the Covid 19 pandemic internationally, as observed by nurses. Methods: An online 52-item questionnaire was used to survey a convenience sample of 369 nurses across North America, Europe and Australasia. Descriptive statistics were used to rank the challenges in caring for PWIDD. Manifest content analysis was used to analyse open-ended responses. This study was approved by the Institutional Ethics Review Board at one of the co-author's educational institution. Results: The quantitative findings from this study were similar across global regions in terms of the challenges faced by people with IDD, including disrupted socialisation with family/friends, limitations to day programming or educational activities, ensuring sufficient staffing to care for people with IDD and coping with pandemic related changes. Qualitative content analysis of open-ended survey responses revealed many challenges for people with IDD during the pandemic which included, issues relating to meaningful socialisation and daytime activation for positive mental/behavioural health and issues regarding access to the quality healthcare care and understating and adapting to changing public health guidelines. Conclusion: Overall this study revealed that the COVID-19 pandemic exposed the existing often unrecognized health and care inequities experienced by people with IDD. Continuing issues with access to care and support for people with IDD in health and social care settings were further impaired by the pandemic. The importance of having meaningful activity and socialization for overall well-being of people with IDD during a long-term public health crisis became very much apparent in the study's findings. This is especially tragic in a group already experiencing inequitable distribution of healthcare, compounding existing disadvantages across a multitude of life domains. These problems are often accentuated by the stigma associated with disability, and a lack of understanding of the healthcare needs of this population. This study benefited greatly from an international collaboration made more possible due great advances in virtual communication during the pandemic.